ELECTRONIC MEDICAL RECORD ACCEPTANCE: A Literature Review - Dewanto, Iwan; Setyonugroho, Winny; Soraya, Ananda Dhea (Acitya Wisesa: Journal of Multidisciplinary Research, 2022)
The implementation of hospital information systems and electronic medical records can improve health care services in hospitals, but there are still many things that inhibits its user acceptance. The purpose of this study is to find out things that can support the acceptance of hospital information systems and medical records by electronic users and their obstacles. This is a literature review research and uses the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) methods.Relevant articles were obtained from PubMed in 1982 to June 2021. Articles were selected if they met the criteria in the form of discussing the acceptance of hospital information systems in the form of electronic medical records in hospitals. The result of this research showed that 1535 articles were obtained from PubMed. The same article was deleted with Zotero's delete duplicate feature and manually with the results of 215 relevant articles, 89 articles were selected through abstract reading and 22 articles were obtained for full text reading.A total of 21 journals were analyzed in this review. Factors that affect the acceptance of hospital information systems and electronic medical records are perceived usefulness, perceived ease of use, human-related factors, demographics and the human environment, technological factors, organizational and organizational environmental factors, effort expectancy and performance expectancy. Implementation of information systems and electronic medical records can be maximized by increasing user acceptance of the system so that health services can be provided optimally.